A Framework for Improving Parent Satisfaction With the Inpatient Pediatric Admission Process: Experience From a Low-Resource Setting. (December 2020) - Hoodbhoy, Zahra; Rasheed, Muneera A; Sherali, Farheen; Hussain, Sehrish; Hassan, Rahmat; Hameed, Aneela; Ali, Rashid; Hasan, Babar
The objective for this initiative was to reduce parental anxiety and thus improve their satisfaction related to hospital admission by ensuring that the child's management plan and basic amenities were communicated to the parents within the first hour of arrival at the Children's Hospital inpatient unit. The intervention for this project was developed based on the Theory of Change framework. Effectiveness of the intervention was assessed by comparing change in parent-reported anxiety scores and improvement in patient satisfaction scores at 24 hours post-admission as an indicator of experience. The frequency of delivery of each individual message was also tracked and compared at baseline and post-intervention. The results showed a significant reduction in parental anxiety levels within the first 24 hours of admission (3.5 to 3.2, P = .01). The parent satisfaction score was significantly improved from baseline to post-intervention (4.00 vs 4.82 respectively; P < .001). Comparison between the baseline and post-intervention demonstrated a statistically significant ( P < .001) increase in frequency of messages delivered. This initiative highlighted that reengineering the current system using existing resources to standardize admission communication along with an adequate monitoring and feedback plan can help reduce parental anxiety, thus improving parent satisfaction with the services.